2020
DOI: 10.1002/2050-7038.12754
|View full text |Cite
|
Sign up to set email alerts
|

PSO optimized PI controlled DC‐DC buck converter‐based proton‐exchange membrane fuel cell emulator for testing of MPPT algorithm and battery charger controller

Abstract: Summary In this article, particle swarm optimized proportional integral (PI) controlled DC‐DC buck converter‐based proton‐exchange membrane fuel cell emulator has been proposed to test the maximum power point tracking algorithm and battery charging controller. Particle swarm optimization is used to optimize the proportional gain (Kp) and integral gain (Ki) of the proportional integral controller for emulating the characteristics of the PEM fuel cell. The simulation model of the proposed PEM fuel cell emulator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…which has a low implementation cost, as shown in (14). In this case, model ( 2) can be expressed as:…”
Section: Unconstrained Nonlinear Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…which has a low implementation cost, as shown in (14). In this case, model ( 2) can be expressed as:…”
Section: Unconstrained Nonlinear Optimizationmentioning
confidence: 99%
“…The RMSE of the Diffusive Global model is 0.3648 V, for the parameters adjusted by ES, 0.7961 V, and for the Gaussian approach it is 0.3567 V. Therefore, the diffusive approach and the Gaussian model have similar predictions of the output voltage. For its low implementation cost, the exponential function of the Gaussian model can be used as shown in the approximation (14) with n = 265. Finally, Figure 8 shows the validation of both approaches, where the RMSE of the diffusive global model and the parameters adjusted by ES were 2.3273 V and 2.3116 V, respectively.…”
Section: Comparison Of Gaussian Model With the Parameter Identification By Means Of Evolution Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…This is yet to be developed. Besides, this study 8 proposed a Particle Swarm Optimized-Proportional Integral (PSO-PI) controlled DC-DC for testing the battery charging controller and the MPPT algorithm. The results revealed that the efficiency of the proposed method is improved.…”
Section: Introductionmentioning
confidence: 99%
“…An emulator was developed to check Maximum Power Point operation of PEMFC using PI controller whose gain was optimized using PSO strategy in Ref. 19. From simulation and experimental results, it was concluded that the proposed emulator was the better choice to check any optimum power tracking controller performance.…”
Section: Introductionmentioning
confidence: 99%